Once upon a time in Venice: The Invention of New Zealand Architecture at the 1991 Mostra di Architettura di Venezia - Wood, Peter (Architectural History Aotearoa, 2020)
There is little in the history of New Zealand that might resonate against measures of architecture established and perpetuated by Euro-centric socio-cultural development. And yet, in 1991, the University of Auckland was judged to have the world's best school of architecture. The circumstances of this recognition followed the Venice Biennale of Architecture that year when, for the first and only time, 43 select architecture programmes were invited to present themselves in open competition in the Corderie dell'Arsenale. The Auckland contribution was an elegant free-standing screen accompanied by a small selection of provocative instrumental drawings, and within the agenda set by the Biennale director, Francesco Dal Co, a claim could indeed have been made that, with this win, New Zealand, at that time, possessed the most eminent School of Architecture in the World. With hindsight the Venice Prize presented a high-takes paradox for New Zealand architecture. Superficially it offered a weighty endorsement for the pedagogic and disciplinary practices of the Auckland School, especially those associated with discursive modes of technical drawing. However, it did so at precisely the moment in history when these modes of representation were declining in the face of digital developments. But this hasn't hindered repeated attempts to duplicate the success in 1991. With this paper I will re-visit The Venice Prize, and subsequent Venetian visitations, with critical attention turned to teasing out some of trials that accompanied these presentations. In particular, thought will be given to how the narrative for New Zealand architecture presented in 1991 has become a prevailing New Zealand architectural mythology, and I will argue that each return to Venice since 1991 has entrenched this narrative as an ever-regressive account of global marginalisation, fragmentation and isolation.